HUBUNGAN PENGETAHUAN DAN PERSEPSI IBU TENTANG STATUS GIZI ANAK DENGAN PERILAKU IBU DALAM PEMBERIAN MAKAN ANAK - Sari, Dyah Purnama; Helmyati, Siti; Sari, Titi Nurma; Hartriyanti, Yayuk (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2021)
Background: One of the factors influencing a child's nutritional status is their mother's or caregivers feeding practice. Mother's behavior in feeding their child is affected by many factors such as social & economic factor, the perception of their child's nutritional status and nutrition knowledge. Objective: To determine the correlation between mothers' knowledge about nutrition and behavior in feeding practice; and the correlation between mothers' perception about their children's nutritional status and behavior in feeding practice (energy, protein, fat, and carbohydrate). Methods: This research was a quantitative study with a cross-sectional design. The samples of this study were 89 pairs of mothers and their child who aged between 1 – 5 years selected by cluster sampling. The subjects of this study took place in HDSS's region, which were Ngaglik and Sleman Districts, Sleman Regency, DI Yogyakarta. This study uses a questionnaire about mothers' perception and knowledge and uses a recall 24-hours to measure the mothers' behavior. The analysis techniques used in this study were Mann Whitney Test and Gamma Test.Results: In general, most mothers have excessive feeding behavior to their child. Mothers with high levels of knowledge tend to have excessive feeding behavior for their child in all nutrients categories. However, mothers with a low level of knowledge tend to have less feeding behavior for energy and fat categories. There are significant correlations between mothers’ knowledge about nutrition with mothers’ feeding practice (p-value <0.001; 0.015; <0.001 and 0.001, respectively). But there is no significant correlation between mothers' perception of their children's nutritional status and mothers' feeding practice for energy, carbohydrate, protein, and fat (p-value 0.854; 0.933; 0.594 and 0.985, respectively). Conclusion: There is a significant correlation between mothers' knowledge about nutrition and mothers' feeding practice. On the other hand, there is no significant correlation between mothers' perception of their children's nutritional status and mothers' feeding practice.